(untitled) (Clinics, 2013)
Azoospermia due to obstructive and non-obstructive mechanisms is a common manifestation of male infertility accounting for 10-15% of such cases. Known genetic factors are responsible for approximately 1/3 of cases of azoospermia. Nonetheless, at least 40% of cases are currently categorized as idiopathic and may be linked to unknown genetic abnormalities. It is recommended that various genetic screening tests are performed in azoospermic men, given that their results may play vital role in not only identifying the etiology but also in preventing the iatrogenic transmission of genetic defects to offspring via advanced assisted conception techniques. In the present review, we examine the current genetic information associated with azoospermia based on results from search engines, such as PUBMED, OVID, SCIENCE DIRECT and SCOPUS. We also present a critical appraisal of use of genetic testing in this subset of infertile patients.